Nexus Between Financial Crises, Corporate Governance and Future Stock Price Crash Risk. (October 2022) - Zulfiqar, Faiza; Sahar, Najam Us; Jalal, Raja Nabeel-Ud-Din; Akhtar, Muhammad; Fayyaz, Um-E-Roman; Venditti, Michelina
We aim to investigate the impact of corporate governance attributes on future stock price crash risk in stable and crisis periods. We used Dynamic Panel Generalized Method of Movements (DPGMM) and Principal Component Analysis (PCA) to generate the factors for the individual attribute to capture the accuracy of the results. Ownership concentration and board structure have a significant negative while audit quality has no association with the stock price crash risk. However, the financial crisis has a positive association with stock crash risk. Furthermore, the study provides a potential screening methodology for investors to mitigate future risk as to price crash risk for portfolios that cannot be dealt with diversification.